2001
DOI: 10.17221/6598-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

The determination of ferulic acid in sugar beet pulp

Abstract: The content of ferulic acid in sugar beet pulp was determined by reverse phase high-pressure liquid chromatography (HPLC) and UV/VIS-spectroscopy. The acid extracts of pectin carrying feruloyl groups were prepared for analysis. To release ferulic acid from pectin the hydrolysis in alkaline medium (pH = 12.5) was performed. Both non-hydrolysed and hydrolysed extracts were measured by UV/VIS-spectroscopy after pH adjustment to the value of 10. The absorbance maximum was observed at 372 nm (ester of ferulic acid)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…FA content of northern Sarawak rice cultivars were analysed using UV-Vis method according to the method developed by Jankovska et al (2001) with minor modification. One gram of rice flour was weighed into a conical flask and added with 100 mL of 0.2 mol/L HCl.…”
Section: Determination Of Ferulic Acid (Fa)mentioning
confidence: 99%
“…FA content of northern Sarawak rice cultivars were analysed using UV-Vis method according to the method developed by Jankovska et al (2001) with minor modification. One gram of rice flour was weighed into a conical flask and added with 100 mL of 0.2 mol/L HCl.…”
Section: Determination Of Ferulic Acid (Fa)mentioning
confidence: 99%
“…Sugar beet pectin (SBP), compared to the main sources of pectin that are citrus and apple, has poorer gelling properties due to its higher content of neutral sugars, low presence of acetyl groups (4–5%) [7], content of ferulic acid, higher protein content [8], and/or its relatively low molecular mass, but in contrast, these molecular characteristics give the SBP better emulsifying properties [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This study has shown that hydrothermal pre-treatment by autoclaving method positively affected the antioxidant activities of corn hydrolysate. This is because many antioxidants, e.g., ferulic acid and p-coumaric acid, are mainly present as esters covalently bound to the cellwall polysaccharides of corn [4,6]. Heat treatment may disrupt the cell wall and release these antioxidants.…”
Section: Effect Of Hydrothermal Pre-treatment On Tpc and Fa Contents mentioning
confidence: 99%
“…FA is usually found as an important structural component of plant cell walls [3,6], located between the lignin and polysaccharide of the cell wall. It covalently attaches to lignin with ether bonds and to polysaccharides with ester bonds.…”
Section: Introductionmentioning
confidence: 99%